Antioxidant activity of Alginate Oligosaccharides (AOS) from Sargassum sp. for Improving the Cutaneous Wound Enclosure in Zebrafish (Danio rerio) - Jelita Rahma Hidayati; Ervia Yudiati; Delianis Pringgenies; Zaneb M. Ben Mansur; Fadhliyah Idris (Universitas Diponegoro, 2021)
Sargassum sp. classified as brown seaweed which is known as an alginophyte (alginate producer). Alginate has undergone a depolymerization process called alginate oligosaccharides (AOS) and has been shown to have antioxidant activities to increase wound tissue recovery. This study aimed to determine the antioxidant activity of Alginate oligosaccharides (AOS) and their ability to improve the cutaneous wound enclosure in Zebrafish (Danio rerio). The IC50 value was used to calculate the ability of extract to inhibit free radicals using DPPH (516 nm). Zebrafish were immersed 12 hours before the injury and shortly after injury with a two factorial design, i.e., alginate concentration and immersion time. Zebrafish were immersed for 1 hour, 3 hours, and 5 hours with serial concentration of 200 ppm, 400 ppm, and 600 ppm, respectively. Morphological observations were carried out at the the first day, fourth day, tenth day, and twenty-first-day post wounding. The results of this study showed that alginate from Sargassum sp. has a yield of 40.5 ± 1.125% with a purity level of 89.95%. Based on antioxidant activity, alginate is categorized as moderate (178,377 ppm) and evidently has the ability to increase wound recovery compared to control. It has indicated by the formation of the wound enclosure.